Pregnancy outcomes in women with gestational diabetes mellitus by models of care: a retrospective cohort study. Issue 9 (26th September 2022) - Harrison, Jackson; Melov, Sarah; Kirby, Adrienne C; Athayde, Neil; Boghossian, Araz; Cheung, Wah; Inglis, Emma; Maravar, Kavita; Padmanabhan, Suja; Luig, Melissa; Hook, Monica; Pasupathy, Dharmintra
Abstract : Objective: To compare birth outcomes of women with gestational diabetes mellitus (GDM) with background obstetric population, stratified by models of care. Design: Retrospective cohort study. Setting: A tertiary referral centre in Sydney, Australia. Participants: All births 1 January 2018 to 30 November 2020. Births <24 weeks, multiple gestations and women with pre-existing diabetes were excluded. Methods: Data were obtained from electronic medical records. Women were classified according to GDM status and last clinic attended prior to delivery. Model of care included attendance at dedicated GDM obstetric clinics, and routine antenatal care. Main outcome measures: Hypertensive disorders of pregnancy (HDP), pre-term birth (PTB), induction of labour (IOL), operative delivery, small for gestational age (SGA), large for gestational age, postpartum haemorrhage, obstetric anal sphincter injury (OASIS), neonatal hypoglycaemia, neonatal hypothermia, neonatal respiratory distress, neonatal intensive care unit (NICU) admission. Results: The GDM rate was 16.3%, with 34.0% of women managed in dedicated GDM clinics. Women with GDM had higher rates of several adverse outcomes. Only women with GDM attending non-dedicated clinics had increased odds of HDP (adjusted OR (adj OR) 1.6, 95% CI 1.2 to 2.0), PTB (adj OR 1.7, 95% CI 1.4 to 2.0), OASIS (adj OR 1.4, 95% CI 1.0 to 2.0), similar odds of induction (adj OR 1.0, 95% CI 0.9 to 1.1) compared with non-GDM women. There were increased odds of NICU admission (adj OR 1.5, 95% CI 1.3 to 1.8) similar to women attending high-risk GDM clinics. Conclusions: Women with GDM receiving care in lower risk clinics had similar or higher rates of adverse outcomes. Pathways of care need to be similar in all women with GDM.